2001
DOI: 10.1177/135910530100600208
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Want Control over their Own Health Care? A Review of Measures, Findings, and Research Issues

Abstract: Across a wide variety of medical settings, patients report that they want detailed information about their condition and their treatment whereas stated desire for input into decision making is skewed more in the direction of physician-only or at least collaborative decision-making. These results, along with the contextual and individual difference factors associated with increased willingness to relinquish control (lower educational level, more serious illness, increasing age), indicate that patients want to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 82 publications
0
57
0
2
Order By: Relevance
“…Empowerment may only be a lip-service with a traditional paternalistic attitude and practice behind it [22]. Or empowerment may not be the actual wish of the patients [23]. Or empowerment is better conducted by direct focus on patient behaviour than by improving provider-patient interaction [24].…”
Section: Introductionmentioning
confidence: 98%
“…Empowerment may only be a lip-service with a traditional paternalistic attitude and practice behind it [22]. Or empowerment may not be the actual wish of the patients [23]. Or empowerment is better conducted by direct focus on patient behaviour than by improving provider-patient interaction [24].…”
Section: Introductionmentioning
confidence: 98%
“…According to current medical models of chronic illness, the practitioner serves as the client's guide in making informed choices about living with illness and making an optimal adaptation, in terms of selfmanagement, functioning, and quality of life. Participating in making health care decisions is assumed to increase the client's engagement, knowledge, confidence, skills, and commitment to making an optimal adjustment (Auerbach, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, over the past 3 decades, the literature has consistently identified that many patients and family members are dissatisfied with cancer education [7]. One of the challenges for cancer education is that patients want more detailed information about their particular type of cancer and other cancer-related issues [2]. Information about treatment options, potential side effects, recovery time, and other cancer-related issues are important aspects of illness that vary considerably depending on cancer type, phase, and prognosis.…”
Section: Discussionmentioning
confidence: 99%